Evaluation of maxillary sinus dimensions and volume using cone beam computed tomography in patients with unilaterally displaced palatal and buccal maxillary canines - Elham S. Abu Alhaija (5959610) (2022)
Objectives To evaluate and compare the maxillary sinus (MS) dimensions and volume in unilaterally displaced palatal and buccal maxillary canines. Methods CBCT images for 133 patients were included in the study. Maxillary canines were unilaterally displaced palatally in 83 patients (PDCs) and buccally in 50 patients(BDCs). The following variables were measured: canine position in relation to MS walls, MS pneumatization and MS dimensions and volume. Results MS was extended to the incisor region in 10% and 13% and to the canine region in 48% and 23% in BDCs and PDCs subjects, respectively. In BDC subjects, maxillary canine crown tip was more laterally (24.23 mm compared to 22.93 mm (p < 0.05)) and closer vertically (5.82 mm compared to 9.58 mm (p < 0.001)) to the MS, maxillary canine root tip was closer to the MS anterior (0 mm compared to 1.64 mm (p < 0.05)) and lateral (19.70 mm compared to 22.02 mm (p < 0.001)) walls and the MS volume (11.57mm3 compared to 9.09 mm3 (p < 0.001)) was increased in the displaced side compared to the non-displaced side. In PDC subjects, a significant difference between the displaced and non-displaced sides was detected in the vertical (3.28 mm compared to 5.89 mm (p < 0.001)) and lateral (21.63 mm compared to 24.25 mm (p < 0.001)) position of maxillary canine to the MS wall, the anterior (− 0.84 mm compared to 1.13 mm (p < 0.05)) and lateral (20.48 mm compared to 22.44 mm (p < 0.001)) position of canine root tip to the MS and the MS volume (7.71mm3 compared to 9.14mm3 (p < 0.001)). PDC sides differed from BDC sides in the lateral and vertical position of canine crown tip to MS and in MS volume. PDC showed negative association with MS volume and anteroposterior skeletal relationship and a positive association with MS height. Conclusions PDCs subjects have a reduced MS volume and BDCs subjects have an increased MS volume. PDCs are associated with reduced MS volume, increased MS height and Class III skeletal relationship. Other Information Published in: Oral Radiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11282-022-00663-6